2002
DOI: 10.1007/3-540-46043-8_107
|View full text |Cite
|
Sign up to set email alerts
|

A Subspace Semidefinite Programming for Spectral Graph Partitioning

Abstract: Abstract.A semidefinite program (SDP) is an optimization problem over n × n symmetric matrices where a linear function of the entries is to be minimized subject to linear equality constraints, and the condition that the unknown matrix is positive semidefinite. Standard techniques for solving SDP's require O(n 3 ) operations per iteration. We introduce subspace algorithms that greatly reduce the cost os solving large-scale SDP's. We apply these algorithms to SDP approximations of graph partitioning problems. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The SDP method for graph partitioning has been studied, e.g., in [49,106]. Oliveira [70] showed that a generalization of graph partitioning, where the vertices have preference values for belonging to a certain partition, can also be modeled as i i 1.5. Beyond traditional models a SDP.…”
Section: Semidefinite Programming For Graph Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The SDP method for graph partitioning has been studied, e.g., in [49,106]. Oliveira [70] showed that a generalization of graph partitioning, where the vertices have preference values for belonging to a certain partition, can also be modeled as i i 1.5. Beyond traditional models a SDP.…”
Section: Semidefinite Programming For Graph Partitioningmentioning
confidence: 99%
“…Subspace algorithms for SDP are analogous to Lanczos/Arnoldi or Davidson-type algorithms for eigenvalue problems. Recent work [70,71,72] indicates that such algorithms for SDP graph partitioning are much faster than full SDP solvers and are competitive with spectral partitioning.…”
Section: Semidefinite Programming For Graph Partitioningmentioning
confidence: 99%